UPAYA INDIAN CULTURAL CENTER DALAM MELAKSANAKAN DIPLOMASI BUDAYA DI BALI - Julita Maharani, Ni Luh Putu Ratih; Kumala Dewi, Putu Ratih; Intan Parameswari, Anak Agung Ayu (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT This research aims to describe the efforts of the Indian Cultural Center (ICC) in implementing cultural diplomacy in Bali. India formed the Indian Council for Cultural Relations (ICCR) whose duty was to play an active role in the cultural external affairs of India. To maximize its performance, the ICCR established a number of cultural centers in various countries as its sub centers. One of them is ICC in Bali. The method used in this research is descriptive qualitative method. This research uses data collected through various sources including interviews, literature studies, reports and news. The data that has been obtained is analyzed with two concepts namely Cultural Diplomacy Tools and Three Secrets of Successful Cultural Diplomacy. The results of this research are the various efforts carried out by the ICC in its various programs and its commitment in working for the success of Indian cultural diplomacy in Bali.. Keywords:Indian Cultural Center, Soft Power, Cultural Center, Efforts of Cultural Diplomacy